FERMI-LAT OBSERVATIONS OF HIGH- AND INTERMEDIATE-VELOCITY CLOUDS: TRACING COSMIC RAYS IN THE HALO OF THE MILKY WAY - Tibaldo, L.; Digel, S. W.; Casandjian, J. M.; Franckowiak, A.; Grenier, I. A.; Jóhannesson, G.; Marshall, D. J.; Moskalenko, I. V.; Negro, M.; Orlando, E.; Porter, T. A.; Reimer, O.; et al. (The Astrophysical journal, 2015)
ABSTRACT It is widely accepted that cosmic rays (CRs) up to at least PeV energies are Galactic in origin. Accelerated particles are injected into the interstellar medium where they propagate to the farthest reaches of the Milky Way, including a surrounding halo. The composition of CRs coming to the solar system can be measured directly and has been used to infer the details of CR propagation that are extrapolated to the whole Galaxy. In contrast, indirect methods, such as observations of γ-ray emission from CR interactions with interstellar gas, have been employed to directly probe the CR densities in distant locations throughout the Galactic plane. In this article we use 73 months of data from the Fermi Large Area Telescope in the energy range between 300 MeV and 10 GeV to search for γ-ray emission produced by CR interactions in several high- and intermediate-velocity clouds (IVCs) located at up to ∼7 kpc above the Galactic plane. We achieve the first detection of IVCs in γ rays and set upper limits on the emission from the remaining targets, thereby tracing the distribution of CR nuclei in the halo for the first time. We find that the γ-ray emissivity per H atom decreases with increasing distance from the plane at 97.5% confidence level. This corroborates the notion that CRs at the relevant energies originate in the Galactic disk. The emissivity of the upper intermediate-velocity Arch hints at a 50% decline of CR densities within 2 kpc from the plane. We compare our results to predictions of CR propagation models.